2005
DOI: 10.1038/ni1257
|View full text |Cite
|
Sign up to set email alerts
|

T cell receptor recognition of a 'super-bulged' major histocompatibility complex class I–bound peptide

Abstract: Unusually long major histocompatibility complex (MHC) class I-restricted epitopes are important in immunity, but their 'bulged' conformation represents a potential obstacle to alphabeta T cell receptor (TCR)-MHC class I docking. To elucidate how such recognition is achieved while still preserving MHC restriction, we have determined here the structure of a TCR in complex with HLA-B(*)3508 presenting a peptide 13 amino acids in length. This complex was atypical of TCR-peptide-MHC class I interactions, being domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
272
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 259 publications
(292 citation statements)
references
References 65 publications
15
272
0
Order By: Relevance
“…Typically, these involve highly related allotypes that exhibit limited sequence differences, which nevertheless often result in biologically significant changes in conformation of the peptide and/or the MHC-I molecule (2,(61)(62)(63). In contrast, despite the comparatively low level of sequence identity between Qa-1 b and HLA-E, remarkably, they present their respective peptide cargoes in a very similar manner for recognition by CD94-NKG2 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, these involve highly related allotypes that exhibit limited sequence differences, which nevertheless often result in biologically significant changes in conformation of the peptide and/or the MHC-I molecule (2,(61)(62)(63). In contrast, despite the comparatively low level of sequence identity between Qa-1 b and HLA-E, remarkably, they present their respective peptide cargoes in a very similar manner for recognition by CD94-NKG2 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…5C). These experiments revealed that the TCRs generated in these four donors were sensitive to amino acid substitution at positions 4,5,6,7,8,9, or 10 of the RPH peptide. These data illustrate the functional diversity generated within the RPHspecific TCR repertoire across the population as a result of the 21.5-kb deletion in the TCR b locus.…”
Section: Structure Of the Rph-hla-b*0702 Complexmentioning
confidence: 99%
“…Despite this vast potential repertoire, immune responses often show strong bias in TCR selection, resulting in immunodominance of certain "public" TCRs that are widely used in individuals with shared MHC types (2)(3)(4)(5). Structural studies have shown that biased TCR usage arises from unique specificity requirements for a given peptide-MHC complex (6,7). Furthermore, TCR production frequency during recombination in the thymus also contributes to bias in TCR usage in Ag-specific responses, with public TCRs generally produced with fewer random nucleotide additions in their sequence (8).…”
mentioning
confidence: 99%
“…This analysis reveals that, for certain locations, particularly in loop regions such as residues 39-42 of the a1-domain and a conspicuous stretch of three residues (149-151) within the N-terminal region of the a2-helix, the positions of the Ca atoms in the two structures differ by more than 1.0 Å. Similar domain-wise analyses of other regions of the structure show Ca shifts larger than 0.5 Å at several positions in the a3 domain and at residues [46][47][48][49]59, and 96-99 in b 2 m. The comparison demonstrates also that the a3-domain has most main chain shifts (0.50-1.13 Å) and differences in side chain orientations, although nearly all residues having such differences are part of loop regions.…”
Section: Structural Features Of the Hla-a1:mage-a1 Complexmentioning
confidence: 82%